Effect of proteolytic enzyme on the chemical and antioxidant properties of low-salt fermented green mussel (Perna viridis) - Escaño, Vanessa Mae
Low-salt (1:5 salt to mussel ratio) fermented green mussel (Perna viridis) was added with 1% crude neutral protease and analyzed for its chemical and antioxidant properties during 56-days fermentation period. The results of this study indicate the potential of producing low-salt fermented green mussel. Additional of 1% crude neutral protease did not effectively increase increase the chemical and antioxidant properties of low-salt fermented mussel. Chemical analyses showed that low-salt fermented mussel without enzyme had higher formol nitrogen, total soluble protein and ammonia nitrogen content indicating higher degree of protein hydrolysis and production of free amino acids. In addition, sample without proteolytic enzyme had higher total phenol content, DPPH radical scavenging activity and ferric reducing antioxidant power indicating its greater potential as good source of antioxidant compounds.